Inheritance Law and Investment in Family Firms - Ellul, Andrew; Pagano, Marco; Panunzi, Fausto (American Economic Review, 2010)
Entrepreneurs may be legally bound to bequeath a minimal stake to noncontrolling heirs. The size of this stake can reduce investment in family firms, by reducing the future income they can pledge to external financiers. Using a purpose-built indicator of the permissiveness of inheritance law and data for 10,004 firms from 38 countries in 1990–2006, we find that stricter inheritance law is associated with lower investment in family firms but does not affect investment in nonfamily firms. Moreover, as the model predicts, inheritance law affects investment only in family firms that experience a succession. (JEL G31, G32, K22, L26, O17).